Federalism and regional coalition: state-level representativeness in Brazilian ministerial portfolios - Codato, Adriano (2023)
Our article analyzes the proportional presence of states and regions in ministerial offices during the administrations of Cardoso, Lula da Silva, and Rousseff. Stemming from the political starting point of 265 ministers, we developed an index to measure the federative coalescence rate of ministerial offices. The index calculates the regional representation proportionality of ministerial staffs year by year across different administrations. Beyond the overrepresentation of São Paulo, Minas Gerais, Rio Grande do Sul, and Rio de Janeiro regarding the effective weight of such states in allied parties within Congress, our results allow us to compare the intensity and evolution of federative coalescence with party coalescence over time for different presidents.